The value of trace minerals in a fattening ration. - Oltjen, R.R.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
This is the fourth in a series of experiments conducted to determine the value of trace minerals in a typical fattening ration. Three previous experiments, similar to this one, were reported in Kansas Agr. Exp. Sta. Cirs. 297, 308 and 335. Chemical analyses of feeds commonly used in cattle rations in this area show there is no deficiency in any of the trace minerals: cobalt, copper, iodine, iron, manganese and zinc. It is possible the minerals may not be adequately balanced or available to the animal at all times. The objective of this test is to determine if trace minerals, when fed at a commonly used level, will influence rate of gain and feed efficiency.
Keywords: Beef; Gain; Trace minerals; Feed efficiency